Anti-jamming transmission in a multi-channel wireless network based on incomplete information dynamic game - Hengjie ZHOU; Minhong SUN; Hua ZHONG; Wei LIU (Dianxin kexue)
Intelligent jammer can analyze the history of user’s transmission and control their own behavior,so it has brought new threats to the wireless network.In order to analyze the behavior of users and intelligent jammers in a multi-channel wireless network,a dynamic Stackelberg game with incomplete information was modelled.In the model,it was assumed that the intelligent jammer followed the user and they transmitted at a same wireless channel,and both of them took power control as their strategy.Furthermore,their benefit functions were designed of which the observation error of the jammer was taken into account.Then,the Stackelberg equilibrium (SE) point of the game model was derived and the existence and the uniqueness of the SE were proved.The validity of the multi-channel dynamic Stackelberg game anti-jamming model with incomplete information was verified by simulations.